Case Study of The Application Warm Water Foot Soak Therapy in The Elderly With Hypertension The Hamlet of Gubuk Pande, Apitaik Village, Pringgabaya Sub-District - Hulyati, Baiq (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension often occurs in the elderly and is a condition in which a person experiences an increase in blood pressure above normal which can result in morbidity and mortality. One of the nonpharmacological treatments for hypertension is foot soak using hanagt water. Warm water is able to provide a relaxing effect that causes a sense of relaxation to cause sopartifik (want to sleep) which can lower blood pressure. Method: This study aims to analyze the use of foot soaks using warm water against insomnia in the elderly to lower blood pressure in hypertensive patients in Gubuk Pande Hamlet, Apitaik Village, Pringgabaya District. The subject of this case study was a patient with hypertension. Result: The results of the treatment showed that after 5 days of intervention, blood pressure dropped from 160/100 mmHg to 150/90 mmHg. Conclusion: The conclusion from the results of this study is that foot soak therapy using warm water can reduce blood pressure in hypertensive patients. It is hoped that medical personnel can improve the quality of service in providing nursing care to patients, especially in Hypertensive Patients with foot soak interventions using warm water.